Advanced Wheat Genotypes Response to Helicoverpa armigera Hubner Infestation: Wheat Genotype Response to H. armigera - Akhtar, Lal Hussain; Tariq, Altaf Hussain; Hussain, Manzoor; Iqbal, Rana Muhammad; Amer, Marghub; Amer, Marghub (Biological Sciences - PJSIR, 2009)
In the evaluation of the response of 20 wheat genotypes in terms of spike and grain damage caused by Helicoverpa armigera Hubner, a significant genotypic variability was found to exist among the wheat genotypes for all the traits studied. Grain yield ranged from 2931 (DN-10) to 4333 (AUP-9701) kg/ha, whereas, spike and grain damage ranged from 19.95 to 80.47 and 3.90 to 22.16% in various wheat genotypes, respectively.